Parental perceptions on the importance of play in early childhood - Ducusin, Ria Jhoanna C.; Dy, Marison Felicidad R. (2016)
This study aimed to explore and compare the factors associated with the perceptions of parents of kindergarten students in private and public schools about play and its importance to children. Seventy-nine parents completed the questionnaire to look into the major factors that affect a parent's perceptions, namely, opinions, experiences, expectations, attitudes, and knowledge. The average scores gathered for these factors, which were computed through Likert scales, served as the level of importance parents give to child play. The differences between the public and private school respondents were compared with average sums. Based on their perceptions of play and its importance to them, both the public and private school respondents had a positive view of play and all agreed that play is important for health, learning and development. In terms of the level of importance given to play, private school respondents had a positive view of play and all agreed that play is important for health, learning and development. In terms of the level of importance given to play, private school respondents had a higher average compared to public school respondents with a percentage difference ranging from 2-8 percent. Overall, private school respondents showed greater imortance given to play in all the major factors that can be affect parental perceptions.
Keywords: Early childhood education; Early Childhood Education - Parent Participation